Anatomy of the Lockerbie bombing: Libya’s role and reactions to al-Megrahi’s release (Glocalism: Journal of Culture, Politics and Innovation, 2015)
Despite its long historical antecedents, terrorism is amongst the growing realities of the national history of contemporary sovereign states. With this emergence, destabilizing influence, and internationalization, terrorism has made the associated security challenge a major diplomatic headache for all key international actors and diplomats. This paper, which adopts a theoretical approach, assesses claims that Ghadafi’s Libya championed state-sponsored terrorism. It reviews the Lockerbie bombing and the conviction of al-Megrahi by the court in Netherland as well as his release from Scottish prison on compassionate grounds. It examines Libya’s use of available diplomatic tools and channels not only to prevent Abdelbaset Ali Mohammed al-Megrahi from facing justice but also to attain Ghadafi’s political and economic interests. This article documents the political communication that followed his release and calls for increased diplomatic investigations of the Lockerbie terrorist attack. Finally, the paper beckons on Libya’s new leaders and the leaderships of USA and Scotland to engage in a progressive multilateral strategic cooperation to unravel further facts on the Lockerbie bombing while promoting the current international “war” against terrorism.
Keywords: al-Megrahi; Ghadafi; bombing; terrorism; prosecution